A comparison of the e-government system architecture in Jordan with the E-government system of the United States - Alhawawsha, Mohammad (Technology audit and production reserves, 2017)
The research seeks to examine the structure of the E-government system in Jordan and comparing it with that of the United States. The research is based on the finding that few researchers have attempted to develop a good analysis of the Jordanian e-government system architecture, especially by making comparisons with those of developed nations like the US. Consequently, there is a knowledge gap in this field, which should be filled by analyzing the nation’s e-government system architecture and comparing it with that of a developed nation. The aim of this study was to determine the structure and composition of the e-government system architecture in Jordan. In particular, the study sought to determine how the structure is set and how it works by analyzing it in comparison to that of the United States, a developed nation and one of the countries that was among the first to adopt e-government systems. The researcher seeks to analyze the e-government architecture adopted in Jordan (a developing nation), to compare the e-government architecture in Jordan with that of the US and to determine the challenges facing the architecture in the country. Based on a qualitative analysis of the e-government system architecture in Jordan and comparing it with that of the United States, the study finds that the E-government system in Jordan has improved service delivery to the citizens because it provides timely, less costly and effective services. Nevertheless, it is prone to information threats and needs continuous improvement. Further, it is also less effective compared to that of the US, especially because the level of hierarchy in the Jordanian government is higher than that of the US. Despite this, it has been found that new e-government system has an advantage because it can continuously be improved by adding new technologies and infrastructure to tackle the above-mentioned problems.